Boundedness for Commutators of Rough p-Adic Hardy Operator on p-Adic Central Morrey Spaces. (16th August 2021) - Sarfraz, Naqash; Aslam, Muhammad; Jarad, Fahd
Abstract : In the present article we obtain the boundedness for commutators of rough p -adic Hardy operator on p -adic central Morrey spaces. Furthermore, we also acquire the boundedness of rough p -adic Hardy operator on Lebesgue spaces.